Factors that Affect Mental Health in Elementary School Children: Scoping Review - Ida Wahyuni; Heni Dwi Windarwati; Fransiska Imavike Fevriasanty (Universitas Aisyah Pringsewu, 2023)
Background: Children's mental health is a condition of harmoniously adapting to themselves, their peers, and their environment. Children can control emotions when playing with their peers and have positive and negative attitudes toward themselves. Children's mental health can affect growth and development in adolescence and adulthood, so it can be instilled early. This study aims to identify the factors influencing mental health in school-age children. Methods: The article search uses articles from the last ten years, from 2013-2022. Search articles using the EBSCO, ProQuest, Google Scholar, and ScienceDirect databases according to the inclusion and exclusion criteria that have been determined. The article identification process uses the PRISMA chart and keywords used to identify relevant studies in this review such as “cause”, “child mental health”, and “primary school”. Results: The results obtained from the search for articles were 41377, with the results of as many as 16 articles that matched the inclusion criteria. The results of the paper show that several factors affect the mental health of elementary school-aged children including peer relationships, bullying, violence by friends, attending physical lessons and exergames, student academies, and support from staff and teachers at school. The conclusion is that the scope of the school can influence the factors that affect mental health and mental health problems of children. Abstrak: Latar Belakang Kesehatan jiwa anak merupakan suatu kondisi anak mampu beradaptasi dengan dirinya sendiri, teman sebayanya, dan lingkungannya secara harmonis. Anak mampu mengontrol emosi saat bermain dengan teman sebayanya serta anak memiliki sikap positif dan negatif terhadap dirinya sendiri. Kesehatan jiwa anak dapat mempengaruhi tumbuh kembang dimasa remaja dan dewasa sehingga, dapat ditanamkan dari sejak dini. Tujuan Kajian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi kesehatan jiwa pada anak usia sekolah. Metode Pencarian artikel menggunakan artikel 10 tahun terakhir yaitu dari tahun 2013-2022. Pencarian artikel menggunakan data base EBSCO, Proquest, Google Scholar, dan scienceDirect sesuai dengan kriteria inklusi dan ekslusi yang sudah ditentukan. Proses identifikasi artikel menggunakan bagan PRISMA, kata kunci yang digunakan untuk untuk mengidentifikasi studi yang relevan dalam review ini seperti “Penyebab”, “kesehatan jiwa anak”,” disekolah dasar”. Hasil yang didapat dari penelusuran artikel yaitu sebanyak 41377, dengan hasil sebanyak 16 artikel yang sesuai dengan kriteria inklusi. Hasil dari artikel terdapat beberapa faktor yang mempengaruhi kesehatan jiwa anak usia sekolah dasar diantaranya hubungan teman sebaya, bullying dan kekerasan oleh teman, mengikuti pelajaran jasmani dan exergames, akademi siswa, dukungan dari staf dan guru di sekolah. kesimpulan yaitu faktor -faktor yang mempengaruhi kesehatan jiwa dan masalah kesehatan kesehatan jiwa anak dapat dipengaruhi oleh ruang lingkup disekolah